Conversation with a future self: A letter-exchange exercise enhances student self-continuity, career planning, and academic thinking. Issue 5 (4th July 2021) - Chishima, Yuta; Wilson, Anne E.
ABSTRACT: We expected that enhanced future self-continuity could benefit students planning future academic and career pursuits, and tested a new method to foster self-continuity. A pilot study demonstrated that future self-continuity predicted academic and career planning and was lower in vocational-oriented than academic-oriented high school students. In Study 1, vocational-track students' future self-continuity was higher after a letter exchange exercise with their future self (send and reply). In Study 2, students randomly assigned to a letter exchange ( send to and reply from future self ) condition showed increases in future self-continuity, career planning, and academic delay of gratification relative to students assigned to a  send-only  condition. Perspective taking with a future self can close the gap between present and future selves.